Analysis of Financial Quality Reporting Submitted by Internal Audit Controlling Systems - Stefania Mariana VOICU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
Internal controls and external audits can be of extreme importance by the information given when it comes to the actions taken internally by the audited entity or by the parties involved with the audited entity in some such way. The correlated actions that could be initiated based on the information obtained from this type of controlling mechanisms can be of crucial importance for all the parties involved (e.g. investors, credit partner institutions, fiscal institutions, etc.). Obtaining and reporting statements from these types of mechanisms have to be interdependently consistent with the findings of the submitted reports. In this article it is examinated, from a theoretical point of view, a stable link between the two mechanisms, in order to minimize the risks of inconsistencies that can occur, involuntarily or intentionally, between the resulted statements following the completion of the controlling acts.